Tokoh Sufi dan Tradisi Lisan: Tradisi Manaqib atau Maca Syekh Abdul Qadir Jaelani di Banten - Malihatunnajiah, Eneng (Department of History and Islamic Civilization, Faculty of Adab and Humaniora, UIN Sunan Ampel Surabaya, 2024)
This paper discusses a charismatic Sufi figure in an oral tradition that still exists in Banten Province as a cultural heritage of local wisdom. This Maca Sheikh or Manaqib tradition contains the reading of the biography and spiritual journey of a Sufi figure named Sheikh Abdul Qadir Jaelani written in a manaqib book. Sufism that exists in this oral tradition can add to the community's spirituality of the role model possessed by Sheikh Abdul Qadir Jaelani. The method used in this paper is the historical method, including heuristics, source criticism, interpretation and historiography. The approach used is religious anthropology to see the religious practices that developed in the Banten community. The results of the research in this paper explain that the Maca Sheikh tradition can be carried out on certain occasions, such as circumcision, marriage, seven months, or during the haul of Sheikh Abdul Qadir jaelani which is carried out by someone who has become a member of the Qodiriyah Naqsyabandiyah thoriqoh. The process includes (1) pre-reading (2) reading (3) post-reading.